Lanthanide Luminescence Modulation by Cation–π Interaction in a Bioinspired Scaffold: Selective Detection of Copper(I). (29th July 2015) - Isaac, Manon; Denisov, Sergey A.; Roux, Amandine; Imbert, Daniel; Jonusauskas, Gediminas; McClenaghan, Nathan D.; Sénèque, Olivier
Abstract A prototype luminescent turn‐on probe for Cu+ (and Ag+) is described, harnessing a selective binding site (log Kass=9.4 and 7.3 for Cu+ and Ag+, respectively) based on the coordinating environment of the bacterial metallo‐chaperone CusF, integrated with a terbium‐ion‐signaling moiety. Cation–π interactions were shown to enhance tryptophan triplet population, which subsequently sensitized, on the microsecond timescale, the long‐lived terbium emission, offering a novel approach in bioinspired chemosensor design.